[Pd]-mediated omega-alkynone cycloisomerization approach for the central tetrahydropyran unit and the synthesis of C(31)-C(48) fragment of aflastatin A - Narute, Sachin B.; Kiran, Neella Chandra; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2011)
A concise assembly of the central tetrahydropyran unit of aflastatin A featuring a Pd-mediated alkynone cycloisomerization to provide a glycal and its subsequent stereoselective hydroboration to deliver the requisite stereochemistry at C(33) and C(34) centers is documented.